Structural Impediments Impacting Early-Career Women of Color STEM Faculty Careers - Johnny C. Woods; Tonisha B. Lane; Natali Huggins; Allyson Leggett Watson; Faika Tahir Jan; Saundra Johnson Austin; Sylvia Thomas (MDPI AG, 2024)
Women of Color faculty continue to experience many challenges in their careers, especially in the science, technology, engineering, and mathematics (STEM) fields. As such, more research is needed that considers structural issues inhibiting their success. Using structuration theory and critical race feminism as a conceptual framework, we conducted semi-structured interviews with 19 faculty and administrators in STEM departments at higher education institutions to investigate their perceptions of structural impediments impacting early-career Women of Color STEM faculty careers. Our findings revealed the need to establish policies that are clear, documented, and transparent. Additionally, incremental approaches to tenure and promotion evaluations should be reconsidered, especially when this approach may position Women of Color faculty to appear as if they are underperforming, when the opposite may be true. Furthermore, as higher education institutions endeavor to diversify the professoriate, this study is significant in enabling institutions and STEM departments to be aware of systemic issues confronting them to make significant inroads in retaining and advancing Women of Color faculty in these disciplines.